THE INFLUENCE OF ORGANIZATION COMMITMENT AND COMPENSATION ON EMPLOYEE PERFORMANCE MEDIATED BY ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Mercy Melinda Putri; Anis Siti Hartati; Agus Haryadi (Jurnal Ekonomi dan Bisnis Airlangga, 2021)
Introduction: The purpose of this study is to describe and explain the influence between variables of Organizational Commitment, Compensation, Organizational Citizenship Behavior (OCB), and Employee Performance.